Imports of Intermediate Inputs and Country Size - Amin, Mohammad (Taylor and Francis, 2014)
The article analyses the relationship between country size and the use of imported intermediate inputs by firms in 76 developing countries. Recent evidence indicates that the use of imported inputs can have a large positive effect on productivity and growth, thus motivating a better understanding of the determinants of foreign inputs. Our results confirm that as is the case with exports, use of imported intermediate inputs is much higher at the extensive and intensive margin in small relative to large countries. Our results for imported inputs are comparable in magnitude with that for exports.